Meningkatkan Minat Belajar Seni Tari Pada Siswa Laki Laki Melalui Model Pembelajaran Motivasi ARCS(Attention, Relevance, Confidence, Satisfaction) - Anjani, Helena Lidya; Yetti, Elindra; Cahyadi, Ojang (Jurnal Pendidikan Tari, 2022)
In the learning process, interest is the main thing that must be owned by each individual, without interest students cannot follow learning properly so that it affects student achievement. The importance of interest in learning in the field of dance because art is a cultural heritage that needs to be preserved and developed. This study aims to increase interest in learning to dance in male students in class VIIF of SMPN 134 Jakarta through the application of the ARCS (Attention, Relevance, Confidence, Satisfaction) motivational learning model. This study uses Classroom Action Research (CAR) with Kurt Lewin's model, using qualitative descriptive data analysis and quantitative statistical analysis. Data collection techniques in the form of observation, questionnaires, interviews and documentation. The study was conducted in two cycles on 17 male students. The results showed an increase in interest in learning by obtaining a pre-cycle score of 70.00%, cycle I 76.94% and cycle II 85.82%. For further research, other learning models can be applied to increase male students' interest in learning so that learning is more interesting, fun and varied to lock students' enthusiasm for learning in dance classes.